Finding smoking hot‐spots: a cross‐sectional survey of smoking patterns by housing tenure in England. (20th January 2019) - Jackson, Sarah E.; Smith, Cheryll; Cheeseman, Hazel; West, Robert; Brown, Jamie
Abstract: Aims: To examine smoking prevalence, motivation and attempts to stop smoking, markers of cigarette addiction and success in quit attempts of people living in social housing in England compared with other housing tenures. Design and setting: A large cross‐sectional survey of a representative sample of the English population conducted between January 2015 and October 2017. Participants: A total of 57 522 adults (aged ≥ 16 years). Measurements: Main outcomes were smoking status, number of cigarettes per day, time to first cigarette, exposure to smoking by others, motivation to stop smoking, past‐year quit attempts and use of cessation support. Covariates were age, sex, social grade, region and survey year. Findings: Adults in social housing had twice the odds of being smokers than those living in other housing types [odds ratio (OR) = 2.09, 95% confidence interval (CI) = 1.98–2.22, P  < 0.001]. Smokers in social housing consumed more cigarettes daily (adjusted mean difference = 1.09 cigarettes, 95% CI = 0.72–1.46, P  < 0.001) and were more likely to smoke within 30 minutes of waking (OR = 1.63, 95% CI = 1.48–1.79, P  < 0.001) than smokers living in other housing types. Prevalence of high motivation to stop smoking was similar across housing types (OR = 1.04, 95% CI = 0.91–1.19, P  = 0.553). The prevalence of quit attempts and use of cessation support within the past year were greater in social compared with other housing (OR = 1.14, 95% CI = 1.03–1.26, P  = 0.011; OR = 1.30, 95% CI = 1.09–1.54, P  = 0.003), but success in quitting was much lower (OR = 0.57, 95% CI = 0.45–0.72, P  < 0.001). Conclusions: In England, living in social housing is a major independent risk factor for smoking. These easily identifiable hot‐spots consist of smokers who are at least as motivated to stop as other smokers, but find it more difficult.